2018
DOI: 10.1007/jhep05(2018)172
|View full text |Cite
|
Sign up to set email alerts
|

Holographic quantum entanglement negativity

Abstract: We advance a holographic conjecture for the entanglement negativity of bipartite quantum states in (1 + 1)-dimensional conformal field theories in the AdS 3 /CF T 2 framework. Our conjecture exactly reproduces the replica technique results in the large central charge limit, for both the pure state described by the CF T 1+1 vacuum dual to bulk the pure AdS 3 geometry and the finite temperature mixed state dual to a Euclidean BTZ black hole respectively. The holographic entanglement negativity characterizes the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
130
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(168 citation statements)
references
References 32 publications
37
130
0
Order By: Relevance
“…The above developments naturally lead to the interesting question of a holographic characterization of the entanglement negativity for bipartite pure and mixed states in dual CF T s [25,26]. In the recent past two of the present authors (VM and GS) in a collaboration, proposed a holographic construction for the entanglement negativity of bipartite pure and mixed states in a dual CF T 1+1 through AdS 3 /CF T 2 framework and its covariant extension [27,28]. This construction was rigorously substantiated through a large central charge analysis employing the monodromy technique in [29], although a bulk proof for this conjecture along the lines of [20] is an outstanding issue.…”
Section: Contentsmentioning
confidence: 93%
“…The above developments naturally lead to the interesting question of a holographic characterization of the entanglement negativity for bipartite pure and mixed states in dual CF T s [25,26]. In the recent past two of the present authors (VM and GS) in a collaboration, proposed a holographic construction for the entanglement negativity of bipartite pure and mixed states in a dual CF T 1+1 through AdS 3 /CF T 2 framework and its covariant extension [27,28]. This construction was rigorously substantiated through a large central charge analysis employing the monodromy technique in [29], although a bulk proof for this conjecture along the lines of [20] is an outstanding issue.…”
Section: Contentsmentioning
confidence: 93%
“…We plan to return to these interesting questions in the future. Let us remark that in [9][10][11] it was suggested that in holographic framework the mutual information, multiplied by a constant, could be a dual to the entanglement negativity E. This was revised by a suggestion [14] that the entanglement wedge cross section E W , supplemented by the backreaction of the hanging minimal (cosmological) surfaces to the geometry, is actually a gravity dual of entanglement negativity. While lots of important work [4,6,7, has been carried out and most obvious inequalities tested, we feel that it is premature to identify E W one way or the other.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one can conceive of a Hamiltonian that keeps ρ T B positive semidefinite for some time interval, indicating a protracted separability or bound entanglement. In such a scenario the patterned derivatives may be functionally different from the Jacobian (20) or Hessian (36), and would need to be treated on a case-by-case basis. However, we have seen in Section III B that our expansion correctly predicts zero evolution of the negativity when ρ T B is positive semidefinite.…”
Section: Discussionmentioning
confidence: 99%
“…(32) to (34). All that remains is to merge the unpatterned Hessians as in (36) to obtain the Hessian with respect to a Hermitian variable. We show these computations in more detail in App.…”
Section: Second Derivative Of the Trace Normmentioning
confidence: 99%